The inverse simulation study of aircraft flight path reconstruction - Blajer, Wojciech; Goszczyński, Jacek A.; Krawczyk, Mariusz (Transport, 2002)
This paper presents a uniform approach to the modelling and simulation of aircraft prescribed trajectory flight. The aircraft motion is specified by a trajectory in space, a condition on airframe attitude with respect to the trajectory, and a desired flight velocity variation. For an aircraft controlled by aileron, elevator and rudder deflections and thrust changes a tangent realization of trajectory constraints arises which yields two additional constraints on the airframe attitude with respect to the trajectory. Combining the program constraint conditions and aircraft dynamic equations the governing equations of programmed motion are developed in the form of differential-algebraic equations. A method for solving the equations is proposed. The solution consists of time variations of the aircraft state variables and the demanded control that ensures the programmed motion realization. First Published Online: 19 Dec 2011